Comparison of Khepera robot navigation by evolutionary neural networks and pain-based algorithm - Liu Xin; Vadakkepat, P.; Tong Heng Lee; Xiao Peng; Pang Ki Kim (Congress on Evolutionary Computation 2002, 2002)
A comparison of mobile robot navigation using evolutionary neural networks and the pain based algorithm is discussed in this paper. The controllers are designed based on evolutionary neural networks and the pain-based algorithms. The performance of the controllers are verified with the Khepera robot.